MAKNA GENDHING–GENDHING BAKU RASULAN DALAM RITUAL SRÈDÈKAN - Nil Ikhwan (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2017)
AbstractThis research focuses on the meaning of rasulan in the Srèdèkan ritual using a combined emic and etic approach. It also discusses the form and structure of rasulan in the Srèdèkan ritual and the standard gendhing performed. The standard gendhing in the Srèdèkan ritual can be divided into two categories, namely larangan and Srèdèkan. Gendhing larangan consist of five gendhing. Gendhing Srèdèkan also consist of five gendhing. The standard gendhing rasulan in the Srèdèkan ritual and the offerings made have an important meaning for the community. The meaning of gendhing larangan, amongst others, is to remind people of their goals, ideas and thoughts about life and their ancestors; to save the lives of people and their descendants in this world; to bring prosperity so that they are never short of food; and to enable them to live a long life, to enjoy time with their children, grandchildren, great-grandchildren, and even great-great-grandchildren, if God is willing. The meaning of gendhing Srèdèkan comes from dahnyang Srèdèk. Keywords: Meaning, Gendhing, Rasulan, Srèdèkan. AbstrakPenelitian ini difokuskan pada makna rasulan dalam ritual Srèdèkan dengan gabungan pendekatan, emik dan etik. Selain itu, dibahas mengenai bentuk maupun tatanan rasulan dalam ritual Srèdèkan serta gendhing – gendhing baku yang disajikan. Gendhing–gendhing baku ritual Srèdèkan terbagi menjadi dua bagian, larangan dan Srèdèkan. Gendhing–gendhing larangan terdiri dari lima gendhing. Gendhing–gendhing Srèdèkan terbagi menjadi lima ge;ndhing. Gendhing–gendhing baku rasulan dalam ritual Srèdèkan dan sesaji yang memberi makna untuk masyarakat. Makna gendhing larangan antara lain; mengingatkan manusia akan tujuan, gagasan fikiran hidup dan leluhur; menyelamatkan hidup manusia di dunia beserta anak cucunya, melancarkan rejeki masyarakat agar pedaringan yang dimiliki selalu penuh; dan agar usia manusi sampai keturunan anak, cucu, buyut bahkan canggah bila Tuhan menghendaki. Makna gendhing baku Srèdèkan ditimbulkan dari dahnyang Srèdèk. Kata Kunci: Makna, Gendhing, Rasulan, Srèdèkan